Exploring early language learning instructional patterns in multilingual English Foreign Language classrooms across South Africa and Zimbabwe - Taringa, Beatrice; Manyike, Tintswalo Vivian (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2026)
African colonial history reshaped the linguistic terrain and complicated language planning in South Africa and Zimbabwe. The coming of the colonial languages brought linguistic inequality which relegated the National Indigenous Languages (NILs) into the periphery. This paper explores stakeholder perceptions of translanguaging in teaching and learning of English Foreign Language (EFL) for selected South African and Zimbabwean primary school learners. The multiple qualitative case study based on constructionist ontology and interpretive epistemology is used in the study. Drawing on ideas of cultural capital theory, four key-informant teachers and four school principals (South Africa) or school administrators (Zimbabwe) were selected through purposive sampling. Data were gathered through two virtual focus group discussion (one per country) using open-ended questions. Data were analysed descriptively using thematic web-like approach. The open and axial coding techniques of grounded theory were applied. The sub-themes, themes and global themes that emerged were constructed and interwoven into a narrative about the participants’ perceptions of translanguaging in multilingual classrooms using EFL as Language of Teaching and Learning (LoLT) (per South African terminology) or EFL as Medium of Instruction (MoI) (per Zimbabwean terminology). Findings revealed that key-informants perceive translanguaging differently and take it both as an asset or liability in EFL learning spaces. For some, it is an instructional pedagogical asset for bridging linguistic gaps in multilingual and multicultural contexts while for some it is a liability that may derail efforts in fostering learner’ English language proficiency. The paper recommends that similar studies be undertaken in other contexts to see if they are echoing the same sentiments.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Volume 10, Issue 1, 2026
Keywords: Code-switching; Language-in-education policy; Code-mixing; Cultural capital theory; Translanguaging; Cultural Relations; Code switching (Linguistics); Translanguaging (Linguistics); Multilingual education -- South Africa; Multilingual education -- Zimbabwe; English language -- Study and teaching; Language policy -- South Africa; Language policy -- Zimbabwe